HUBUNGAN SELF-EFFICACY TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIK SISWA SMP PADA MATERI BANGUN DATAR SEGITIGA DAN SEGIEMPAT - Wulansari Wulansari; Asep Ikin Suganda; Aflich Yusnita Fitriana (Departement of Mathematics Education, 2019)
This study aims to determine the relationship of self-efficacy to the mathematical creative ability of junior high school students in the material of flat triangles and quadrilateral. The method used is quantitative by correlation method. This research was conducted in one of the Public Middle Schools in Cimahi City with a population of all students in class VII and a sample of class VII-5 as many as 30 people. The test is done by giving a question of the ability to think creatively as many as 5 items and the scale of self-efficacy with a Likert scale. The steps used in the analysis, namely normality test, korealsi test, determine the determinant coefficient or determinant coefficient to see the contribution or influence of the variable self-efficacy on mathematical creative thinking abilities of middle school students. Based on the results of the study showed that there was a significant relationship between self-efficacy on the ability of creative thinking of junior high school students, and the large contribution given by self-efficacy to mathematical creative thinking skills was 16.00%.